Strategy for Overcoming the Spread of COVID-19 During the Pandemic - Lubis, Ika Syani Putri (Journal of Health Science and Medical Therapy, 2023)
The increasing number of people affected by the Covid-19 virus is due to society's lack of preparation for the arrival of this disease. Today's pandemic conditions have increased the number of victims every time, so a strategy is needed to overcome the spread of COVID-19. The research location in this study was at several health institutions, and data was collected from various communities. The research location was carried out in the city of Medan through various health agencies. The research results show that maintaining distance and using medical equipment such as masks are the right strategies to overcome the spread of COVID-19. This is proven by various communities starting to comply with the rules, and the spread of COVID-19 can be reduced. This research concludes that maintaining distance and using masks is the most appropriate strategy for reducing the spread of COVID-19 in Medan.